Experiment study on the performance of temperature calibration methods - Ngai, Xuan Dong (2018)
Different methods of calibration were experimented for Negative Temperature Coefficient thermistor. The different methods were beta formula, non-linear least square, inverse calibration and QR decomposition. To carry the experiment, a reference thermometer was used together with a thermistor to record the corresponding temperature and resistance. A digital multimeter was used to measure the resistance of the thermistor. They were placed in a thermo-flask with water so that the data points can be collected at different temperature, forming a non-linear relationship between temperature and resistance. The errors were compared on MATLAB and the method with the least errors were converted to C programming and downloaded to a micro controller for verification.